Effect of Ionizing Radiation Applied to PLA Used as Compatibilizing Agent in Reinforced eGG Shell PBAT/PLA Bio-Based Composites - Cardoso, Elizabeth C.L.; Parra, Duclerc F.; Scagliusi, Sandra R.; Komatsu, L.G.H.; Lugão, Ademar B. (Journal of Research Updates in Polymer Science, 2021)
Bio-filler from eggshells as reinforcement of bio-based polymers are based on their benefits as adequate strength and stiffness, besides friendly, degradable and renewable environment. Eggshell is an agricultural waste considered as garbage, contributing to pollution; nevertheless, it can be transformed into bio-calcium carbonate, acquiring new values. As biodegradable polymers, there were chosen PLA (poly-lactic-acid) and PBAT (butylene adipate co-terephthalate), thermoplastics capable to be processed via conventional methods. PLA is a linear, aliphatic thermoplastic polyester, high in strength and modulus, but brittle. PBAT is a synthetic polymer, very flexible, based on fossil resources with high elongation at break, but low strength. It will be required the use of compatibilizers, for reducing interfacial tension exhibited by PLA/PBAT immiscible blend, considering their extreme glass transition temperatures: 62 o C for PLA and – 30 o C for PBAT. Herein it was used ionizing radiation for inducing compatibilization by free radicals, improving dispersion and adhesion of blend phases, without using chemical additives, at room temperature. PLA, acting as compatibilizer, was previously e-beam and gamma radiated, at 150 kGy. PBAT/PLA 50/50 blend with 15 phr of bio-filler from avian eggs 125 µm particle size and both compatibilizers were homogeneized in a co-rotating twin-screw extruder, within a temperature profile 120 to 145 o C, from hopper to die. Characterization involved: Differential Scanning Calorimeter, Thermogravimetric Analyses, Fourier Transform Infrared Spectroscopy, Wide Angle X-Ray Diffraction, Tensile Strength and Elongation at Break.